High-sensitivity troponin and novel biomarkers for the early diagnosis of non-ST-segment elevation myocardial infarction in patients with atrial fibrillation. Issue 6 (1st October 2016) - Sörensen, Nils A; Shah, Anoop S V; Ojeda, Francisco M; Peitsmeyer, Philipp; Zeller, Tanja; Keller, Till; Johannsen, Silke S; Lackner, Karl J; Griffiths, Megan; Münzel, Thomas; Mills, Nicholas L; Blankenberg, Stefan; et al.
Abstract: Aims: To evaluate the diagnostic performance of high-sensitivity troponin I (hsTnI) and other novel biomarkers for diagnosing non-ST-segment elevation myocardial infarction (NSTEMI) in patients with atrial fibrillation. Methods: In an acute chest pain cohort (N=1673), mean age 61.4±13.6 (34% female), we measured hsTnI and 13 established and novel biomarkers reflecting ischaemia, necrosis, inflammation, myocardial stress, angiogenesis on admission and after three hours in order to investigate their diagnostic accuracy for NSTEMI. Results: In atrial fibrillation patients ( N =299) hsTnI on admission had the best discriminatory ability for NSTEMI (area under the curve 0.97) with only two novel biomarkers, copeptin and heart-type fatty acid binding protein, having area under the curve >0.70. Measured biomarkers showed comparable discriminatory ability in atrial fibrillation and non-atrial fibrillation patients. The combination of hsTnI on admission with additional biomarkers did not clinically significantly improve diagnostic performance. In atrial fibrillation patients, hsTnI concentrations ⩽21.7 ng/L (99th percentile in a healthy German cohort) on admission gave a negative predictive value of 100% (95% confidence interval 97–100%). The combination of hsTnI on admission and absolute change of hsTnI concentration after three hours of ⩾40 ng/L resulted in a positive predictive value of 81.2% and sensitivity of 88.6%. Diagnostic accuracy was validated in an independent cohort ( N =1076). Conclusion: The diagnostic accuracy of hsTnI in patients with acute chest pain and atrial fibrillation is high and comparable to those without atrial fibrillation. Absolute change in hsTnI concentration enhanced diagnostic performance. No clinically relevant improvement was achieved by adding other biomarkers.